The SISTEM PENGOLAHAN DATA INVENTARIS PERALATAN PRAKTEK PADA SMK PRASASTI KARANG BERAHI KOTA JAMBI - Budiarti, Rike Limia; Wahid, Nur (FORTECH (Journal of Information Technology), 2017)
Backgrounds found in SMK Prasasti Karang Berahi Jambi City in the data processing system is still relatively modest inventory, equipment inventory data collection practices done manually with write / record the diary and most of inputting data using Microsoft Office applications , To support these activities need to be made or drafted a pragram or applications that can be used together and were able to run on all computers that have installed the software browsing. Hardware Inventory Data Processing System The practice is built using web-based technology with scripting language PHP, MySQL database, and Freamwork. Implementation of Data Processing System Inventory This web-based SMK Prasasti Karang Berahi so influential for schools, etc., and assist staff in delivering administrative data collection hardware inventory data are ofline and online practice for the data presented quickly.